2008
DOI: 10.1080/03043790802588383
|View full text |Cite
|
Sign up to set email alerts
|

PhD students’ work conditions and study environment in university- and industry-based PhD programmes

Abstract: During the last 10 years, new models of funding and training PhD students have been established in Denmark in order to integrate industry into the entire PhD education. Several programmes have been conducted where it is possible to co-finance PhD scholarships or to become an employee as an industrial PhD in a company. An important question is what impact these new conditions will have on the PhD students' training, work conditions and study environment. In this article, the new type of programmes will be prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 4 publications
2
37
0
2
Order By: Relevance
“…Interestingly, internationals reported a higher overall satisfaction with their experience as a PhD student in the same study. In Denmark, international PhD candidates experience their work environment as less stressful than their Danish counterparts (Kolmos, Kofoed, & Du, 2008). These latter two findings may be related to the literature on job satisfaction as described above: international PhD students may compare their situation to the situation of PhD students in their home country and feel that in comparison, their own situation is better, leading to high satisfaction levels.…”
Section: Previous Studies On the Effect Of Phd Status And Other Charamentioning
confidence: 49%
“…Interestingly, internationals reported a higher overall satisfaction with their experience as a PhD student in the same study. In Denmark, international PhD candidates experience their work environment as less stressful than their Danish counterparts (Kolmos, Kofoed, & Du, 2008). These latter two findings may be related to the literature on job satisfaction as described above: international PhD students may compare their situation to the situation of PhD students in their home country and feel that in comparison, their own situation is better, leading to high satisfaction levels.…”
Section: Previous Studies On the Effect Of Phd Status And Other Charamentioning
confidence: 49%
“…A strong belief of both the candidate and the supervisor was that a warm supportive relationship was important for successful candidature. As reflected in the literature, it is a relationship that goes beyond that of the traditional student academic role (Connell & Manathunga, 2012;Kolmos et al, 2008;Maxwell & Smyth, 2011;Minichiello & Kottler, 2010). Being cognisant of reasons for becoming a PhD supervisor (Lidell et al, 2008) is important as the actions and reactions of the supervisor may be based on their personal PhD experience, which is often the case (Hammond, Ryland, Tennant, & Boud, 2010) and on untested and perceived expectations of the candidate.…”
Section: Supportive Environmentmentioning
confidence: 95%
“…Peer assessment has been studied in various situations and actively pursued as a means by which students are given more control over their learning and achievement [5]. In order to integrate industry into the entire PhD education, new models of funding and training PhD students have been established [6]. The results of this study showed that there were no significant differences between PhD students in traditional university PhD programmes and PhD students in an industrial programme concerning the working environment.…”
Section: Introductionmentioning
confidence: 95%